Evaluation of the hydraulic and hydrodynamic parameters influencing photo-catalytic degradation of bio-persistent pollutants in a pilot plant. Issue 10 (3rd October 2019) - Petrella, Andrea; Spasiano, Danilo; Cosma, Pinalysa; Rizzi, Vito; Race, Marco
Abstract: A kinetic study on the photo-catalytic degradation of bio-persistent micro-pollutants, as methyl red and methylene blue dyes, was carried out on an innovative unit by changing the hydraulic and hydrodynamic parameters of the system. The catalyst (TiO2, anatase) was embedded into a cement matrix and deposited at the bottom of a channel to activate the UVB photo-degradation reactions. The influence of the catalyst dosage, substrate concentration c 0, and pH was evaluated on the degradation rates. The optimum catalytic dose was obtained at 0.79 g/cm 3 while the best results were observed at 0.7 mg/L influent dye concentration. The pH of the solution influenced the sorption phenomena because the charge of the substrates functional groups as well as the charge of the catalyst surface were affected by this parameter. Different unit geometries, hydraulic loads ( hw ) and gradients ( i ) affected speed and flow-rate ( Q ) of the liquid phase and, as a consequence, the irradiated retention times (Irt) of the substrates to the UV/TiO2 system. Kinetics resulted faster at increasing flow-rates of the liquid flowing through the channel, constant the hydraulic load, whereas the increase in the hydraulic load did not improve the performances. Finally, degradation rates slightly decreased after the increase in the hydraulic gradient of the channel.